Picea jezoensis (Sieb. et Zucc.) čiekuri - Jamonte, Daiga (My University, 2019)
Latvijas Universitātes Muzeja Botānikas un mikoloģijas kolekciju ekspozīcijā “Čiekuri” apskatāmi 12 dažādu egļu sugu čiekuri, starp tiem arī hokaido jeb ajānu egles čiekuri. Tas ir Tālajos, Austrumos augošs koks, kur tam ir plašs pielietojums. Latvijā to sāka audzēt 19. gadsimta beigās, bet arī šobrīd tas ir dendroloģisko stādījumu retums.

The exposition “Cones” in the Botanical and Mycological collections of the Museum of the University of Latvia includes cones of 12 different spruce species, among them also cones of the Picea jezonensis. It is a tree growing in the Far East, where it is widely used. It was first introduced in Latvia at the end of the 19th century, but it is still a rarity in dendrological plantations.
Picea jezoensis (Sieb. et Zucc.) cones
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Picea jesonensis; dendrology; čiekuri